Understanding Trends, Influences, Intellectual Structures, and Future Directions in Agrivoltaic Systems Research: A Bibliometric and Thematic Analysis - Altyeb Ali Abaker Omer; Fangxin Zhang; Ming Li; Xinyu Zhang; Feng Zhao; Wenhui Ma; Wen Liu (World)
Agrivoltaic (AV) systems have emerged as a transformative solution to global challenges in food–energy–water security, climate resilience, and sustainable land use. The purpose of this study is to analyze trends, influences, intellectual structures, and future research directions in AV systems research from 2011 to 2023. Using a bibliometric approach guided by the PRISMA framework, 477 documents from the Scopus database were analyzed through performance analysis and science mapping with Bibliometrix and VOSviewer. Key findings reveal exponential growth in research output, with the United States, France, and Germany leading in publications, citations, and international collaboration. Eight thematic clusters were identified, including dual productivity of land use, renewable energy integration, policy implications, and climate adaptation. Influential contributors, such as Joshua M. Pearce, and leading journals, including Applied Energy, shape the field. Emerging areas focus on advanced photovoltaic materials and integrated resource management strategies. This study provides a comprehensive roadmap for advancing AV systems research by identifying critical trends, proposing innovative solutions, and fostering interdisciplinary collaborations. Despite limitations, such as database dependency, this analysis highlights AV systems’ transformative potential to achieve global sustainability goals.